Anatomical features of the palatal root canal in maxillary first molars and their influence on endodontic procedure - Beljić-Ivanović Katarina; Ivanović Vladimir (Serbian Medical Society - Dental Section, Belgrade, 2008)
Introduction: More detailed acquaintance with specialist endodontic literature and treating complicated endodontic cases have revealed that the palatal root canal in maxillary first molars has different features from generally accepted simplicity. Aim: The aim of this study was to investigate the number, orientation and shape of the curvature of the palatal root canal in maxillary first molars, characteristics that may have great influence on the procedure and outcome of endodontic therapy. Materials and methods: Material consisted of 100 left and 100 right extracted human first maxillary molars. Extended access cavity was prepared, and canal orifices were detected using an endodontic probe. K-flex file no 15 or 20 was then introduced into the palatal root canal until the tip appeared at the apical foramen. The tooth was radiographed from buccal-oral (clinical) and mesial-distal (proximal) aspect under standardized conditions. On magnified images, the number and character of canal, orientation and shape of the curvature were determined. Results: One palatal root canal was found in each of 200 teeth. From the clinical projection, 60% of the palatal canals appeared curved and from the proximal 93.5% (p<0.05). Out of 120 curved canals from the clinical aspect, 66.7% were oriented distally and 33.3% mesially. From the proximal projection, of 187 curved canals 68,4% were oriented buccally, and 31,6% palatally. From the clinical projection, 49.2% were C-shaped, and 32.5 % with the J-shaped curvature. Only 18.3% of the palatal canals were with the S-shaped curvature (p<0.05). Conclusions: Upon presented results, practitioners may predict with high significance the character, orientation and curvature shape of the palatal root canal in maxillary first molars in the buccal-oral dimension which is not visible on clinical radiographs and, therefore, perform more successful endodontic treatment.